Costa Rica a traveler's literary companion - Ras, Barbara (San Francisco Whereabouts Press, 1994)
Contributors: Alfredo Aguilar, Fabian Dobles, Carlos Luis Fallas, Jaoquin Gutierrez, Carmen Lyra, Yolanda Oreauno, Julieta Pinto, Carlos Salazar Herrera, Rima de Vallbona, and more.
Northern Zone: Believe it or not / Carmen Naranjo -- The girl who came from the moon / Jose Leon Sanchez -- Bucho Vargas, healer and medicine man / Mario Gonzalez Feo -- San Jose and the Central Valley: The lizard with the white belly / Yolanda Oreamuno -- The chumico tree / Rima de Vallbona -- The targua tree / Fabin Dobles -- The adventure / Samuel Rovinski -- Monday / Fernando Duran Ayanegui -- Faust in Hatillo / Alfonso Chase -- Guanacaste: Mystery stone / Rima de Vallbona -- Southern Pacific Coast: The bongo / Carlos Salazar Herrera -- She wore a bikini / Alfonso Chase -- Southern Zone: The carbonero / Carlos Salazar Herrera -- Atlantic Zone: The diary / Fabian Dobles -- In the shadow of the banana tree / Carlos Luis Fallas -- The oropendolas / Quince Duncan -- from Deeper than skin / Abel Pacheco -- The blue fish / Julieta Pinto -- Costa Rica: The spirit of my land / Yolanda Oreamuno -- Ten little old men / Carmen Lyra -- A leaf of air / Joaquin Guitierrez -- The palmitero / Max Jimenez -- Here / Louis Ducoudray -- We have brought you the sea / Uriel Quesada -- Mint flowers / Alfredo Aguilar -- When new flowers bloomed / Carmen Naranjo.
Keywords: Short stories, Costa Rican -- Translations into English; Costa Rican fiction -- 20th century -- Translations into English